Biosignature detection by Mars rover equivalent instruments in samples from the CanMars Mars Sample Return Analogue Deployment. (15th October 2019) - Stromberg, Jessica M.; Parkinson, Alexis; Morison, Matthew; Cloutis, Edward; Casson, Nora; Applin, Daniel; Poitras, Jordan; Marti, Arola Moreras; Maggiori, Catherine; Cousins, Claire; Whyte, Lyle; Kruzelecky, Roman; et al.
Abstract: This work details the laboratory analysis of a suite of 10 samples collected from an inverted fluvial channel near Hanksville, Utah, USA as a part of the CanMars Mars Sample Return Analogue Deployment (MSRAD). The samples were acquired along the rover traverse for detailed off-site analysis to evaluate the TOC and astrobiological significance of the samples selected based on site observations, and to address one of the science goals of the CanMars mission: to evaluate the ability of different analytical techniques being employed by the Mars2020 mission to detect and characterize any present biosignatures. Analytical techniques analogous to those on the ExoMars, MSL and the MER rovers were also applied to the samples. The total organic carbon content of the samples was <0.02% for all but 4 samples, and organic biosignatures were detected in multiple samples by UV–Vis–NIR reflectance spectroscopy and Raman spectroscopy (532 nm, time-resolved, and UV), which was the most effective of the techniques. The total carbon content of the samples is < 0.3 wt% for all but one calcite rich sample, and organic C was not detectable by FTIR. Carotene and chlorophyll were detected in two samples which also contained gypsum and mineral phases of astrobiological importance for paleoenvironment/habitability and biomarker preservation (clays, gypsum, calcite). They were detected and characterized by multiple techniques, of which passive reflectance was most effective. The sample selected in the field (S2) as having the highest potential for TOC did not have the highest TOC value, however, when considering the sample mineralogy in conjunction with the detection of organic carbon, it is the most astrobiologically relevant. These results highlight the importance of applying multiple techniques for sample characterization and provide insights into their strengths and limitations. Highlights: Detection and characterization of organic carbon and biomolecules by multiple rover-equivalent instruments. Detection and characterization of astrobiologically relevant mineral phases. Application of lab-based techniques analogues to instrumentation from multiple rover missions.